Modulation of the leniency bias in the discursive dilemma. (6th November 2018) - Bodanza, Gustavo; Freidin, Esteban; Linares, Sebastián; Delbianco, Fernando
Abstract : We experimentally approach the discursive dilemma to gain insight into people's procedural appropriateness judgments. We relied on a vignette in which three people had formed opinions about two skills (premises) of a candidate to decide whether to hire her/him (conclusion). The dilemma arises when different outcomes (hire vs. not hire) are achieved depending on whether the majority opinion is independently considered for each premise or for the global conclusion of each judge. Participants were asked to choose the procedure they thought to be more appropriate to reach a decision. In Experiment 1, we found a leniency effect (a bias to prefer the aggregation procedure that led to hiring the candidate), which was reduced by introducing the participant as a juror with an exogenously provided negative opinion about the candidate's skills. In Experiment 2, we replicated the opinion effect, even when subjects did not participate as jury members. In Experiment 3, we found that the leniency bias was only reduced when participants' negative opinion was aligned with a majority of negative premises, but not with a majority of negative conclusions. We discuss present findings in terms of the identification of empirical regularities that may affect people's procedural legitimacy judgments.